Relationship between sleeping quality and behavioural outcomes of UiTM Seremban 3 Students / Nadiah Diyana Tan Abdullah, Radzliyana Radzuwan and Muhammad Nazrie Ab Dini - Tan Abdullah, Nadiah Diyana; Radzuwan, Radzliyana; Ab Dini, Muhammad Nazrie (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Purpose: To examine the relationship between sleeping quality and behavioural outcomes of UiTM Seremban 3 students. Methods and sample: A quantitative approach using a modified questionnaire of Pittsburgh Sleep Quality Index Score was employed to examine the sleeping quality and modified version of the Adolescent Behavioral Checklist was used to obtain the response on the behavioural of UiTM Seremban 3, students. 428 respondents from three (3) faculties in the Seremban campus participated in this study. Findings: The result shows that there is a significant relationship between sleeping quality and behavioural outcomes of the students (r=.118, p<0.05). Discussion and Conclusion: This study revealed that there is no significant relationship between sleeping quality and positive behavioural outcomes. However, the result indicated that there is a weak relationship between sleep quality and negative behavioural outcomes. The behaviours of the respondents tend to become more negative if they were having poor quality of sleep. The results also suggest that poor sleep quality is not only prevalent among college students but are also associated with negative behavioural outcomes. Therefore, sleeping quality should be considered in the management of students’ health and there is a need for an investigation for possible intervention on sleeping quality of the college students.